Potential Roles of Anti-Inflammatory Plant-Derived Bioactive Compounds Targeting Inflammation in Microvascular Complications of Diabetes - Yahia A. Kaabi (Molecules, 2022)
Diabetes mellitus (DM) is a group of metabolic disorders, the characteristics of which include chronic hyperglycemia owing to defects in insulin function, insulin secretion, or both. Inflammation plays a crucial role in DM pathogenesis and innate immunity in the development of microvascular complications of diabetes. In addition, hyperglycemia and DM mediate a proinflammatory microenvironment that can result in various microvascular complications, including diabetic nephropathy (DNP), diabetic neuropathy (DN), and diabetic retinopathy (DR). DNP is a major cause of end-stage renal disease. DNP can lead to albuminuria, decreased filtration, mesangium expansion, thickening of the basement membrane, and eventually renal failure. Furthermore, inflammatory cells can accumulate in the interstitium and glomeruli to deteriorate DNP. DN is another most prevalent microvascular complication of DM and the main cause of high mortality, disability, and a poor quality of life. DNs have a wide range of clinical manifestations because of the types of fiber dysfunctions and complex structures of the peripheral nervous system. DR is also a microvascular and multifactorial disease, as well as a major cause of visual impairment globally. Pathogenesis of DR is yet to be fully revealed, however, numerous studies have already confirmed the role of inflammation in the onset and advancement of DR. Despite evidence, and better knowledge regarding the pathogenesis of these microvascular complications of diabetes, there is still a deficiency of effective therapies. Bioactive compounds are mainly derived from plants, and these molecules have promising therapeutic potential. In this review, evidence and molecular mechanisms regarding the role of inflammation in various microvascular complications of diabetes including DNP, DN, and DR, have been summarized. The therapeutic potential of several bioactive compounds derived from plants in the treatment of these microvascular complications of diabetes has also been discussed.